Factors associated with an excellent outcome after conservative treatment for patients with proximal cervical spondylotic amyotrophy using electrophysiological, neurological and radiological findings. (1st November 2020) - Imajo, Yasuaki; Kanchiku, Tsukasa; Suzuki, Hidenori; Nishida, Norihiro; Funaba, Masahiro; Taguchi, Toshihiko
Abstract : Objective: To investigate factors associated with excellent outcomes after conservative treatment in patients with proximal cervical spondylotic amyotrophy (CSA) using electrophysiological, radiological, and neurological findings. Design: Retrospective study. Setting: Yamaguchi University Hospital. Participants: Seventy-seven patients. Interventions: Erb-point-stimulated compound muscle action potentials (CMAP) were recorded in deltoid and biceps. The percentages of CMAP amplitudes on the affected side compared to the normal side in deltoid (PD) and biceps brachii (PB) were calculated. Central motor conduction time was calculated by subtracting peripheral motor conduction time from the onset latency of motor evoked potentials. Cervical lordotic angles, the diameter of C5 canal, and the intervertebral range at C4–C5 and C5–C6 levels were assessed on plain radiographs. Magnetic resonance imaging was used to assess the width of the intervertebral foramen (WIF) at C4–C5 and C5–C6 levels in the axial views. First visit and final follow-up strengths of most atrophic muscles were evaluated using manual muscle testing (MMT). Improvements in strength were classified as excellent (five grades recovered), good (more than one grade recovered), unchanged (no improvement), or poor (worsened). Results: The outcomes were excellent in 27 patients (35.1%), good in 22 (28.6%), unchanged in 26 (33.8%), and poor in two (2.5%). Factors associated with excellent outcomes were WIF at C4–C5 and C5–C6 on the normal side, PB, and CMAP amplitudes of the deltoid on the normal side. Conclusions: Patients with excellent outcomes originally had wide WIF at C4–C5 and C5–C6 levels and the absence of symptomatic spinal cord compression at C3–C4 and C4–C5 levels.